Demanding Social Issues in the Context of Island Communities - Nikodemus Niko; Azhari Setiawan (Social Issues Quarterly, 2022)
Demanding social issues are essential to social science because they represent complex challenges that impact individuals and communities at multiple levels, including economic, political, cultural, and social. Social scientists play a critical role in understanding and addressing these issues, bringing analytical and empirical methods to bear on complex social problems. The study of social issues involves analyzing the causes and consequences of social problems, identifying potential solutions, and evaluating the effectiveness of different interventions. Social scientists use various research methods, including surveys, interviews, case studies, and statistical analysis, to better understand these issues and their impact on society.